Peripheral substitution as a tool for tuning electron-accepting properties of phthalocyanine analogs in intramolecular charge transfer - Cidlina, Antonin; Novakova, Veronika; Miletin, Miroslav; Zimcik, Petr (Dalton transactions (Cambridge, England, 2015)
The intramolecular charge transfer (ICT), which is a pathway for excited state relaxation, was studied on the newly synthesized zinc(ii) complexes of tetrapyrazinoporphyrazines bearing one fixed donor (i.e., a dialkylamino substituent). The rest of the peripheral substituents on the core was designed with respect to their different electronic effects (OBu, neopentyl, StBu, COOBu). The photophysical (singlet oxygen and fluorescence quantum yields) and electrochemical (reduction potentials) properties were determined and compared within the series and with compounds that did not contain a donor moiety. The ICT efficiency correlated well with both the electron-deficient character of the core and the Hammett substituent constants σp. The most efficient ICT was observed for the core with the most electron-accepting substituent (COOBu), and the lowest ICT efficiency was detected for the least electron-deficient core (substituted by OBu). Titration of DMSO solutions of target compounds with H2SO4 indicated that basicity of the azomethine bridges was largely influenced by the character of the peripheral substituents while the dialkylamino donor center remained nearly unaffected. Furthermore, protonation of the donor nitrogen caused partial restoration of the fluorescence quantum yield (increase up to 90 times) due to blocking of ICT. The results implied that the ICT efficiency was strongly dependent on the electron-accepting properties of the core whose properties can be readily affected by suitable selection of peripheral substituents.
Keywords: fluorescence; elektrochemie; Spectrophotometry, Ultraviolet; indoly; Organometallic Compounds; singletový kyslík; Singlet Oxygen; organokovové sloučeniny; elektrony; Electrons; spektrofotometrie ultrafialová; Fluorescence; Zinc Compounds; Indoles; Isoindoles; isoindoly; Electrochemistry; sloučeniny zinku